Geography and ethics III: Whither the next moral turn?. (December 2018) - Olson, Elizabeth
The 20 years since geography's 'moral turn' have generated a robust field of scholarship around diverse ethical engagements. However, as geographers continue to build articulate claims to care and justice in and beyond the academy, the role of 'the moral' has often been resigned to the margins of our theories and empirical work. In my third and final progress report on geography and ethics, I suggest that new approaches toward moral geographies and economies are already signaling directions for geography's next moral turn. Some of these approaches use more traditional theoretical and empirical options to explain and raise challenges for confronting harmful moral projects endorsed by states. But other more critical and controversial shifts are also evident in the speculative ethics of post-humanism which destabilize and reassemble what we think we know about moral status and moral agency.